Human resource factors on customer satisfaction in emergency call centers of power distribution companies - Bonyadi, Mahmood (2020)
The present study aimed to explore the human factors associated with employees shaping customer satisfaction in the field of emergency call centers of power distribution companies. The literature was reviewed in a range of different disciplines including quality of service, human resource management and marketing. The statistical population of this study is consisted of all employees of emergency call centers of power distribution companies, among whom, according to Krejcie & Morgan (1970) table, the minimum sample size for this study is 285 people. The sampling method of this study was complete random method and the questionnaires were distributed among the selected sample. Dorna et al. (2018) questionnaire was used to measure the variables. The study results show that the factors of human resource management lead to job plan, employee satisfaction, employee efficiency, customer satisfaction, employee retention, training, employee performance, and ultimately organizational performance. Managers of emergency call centers of power distribution companies should note that investing in human resource practices helps to improve customer satisfaction in emergency call centers of power distribution companies.